Integration of large‐area optical imagers for biometric recognition and touch in displays. Issue 12 (24th May 2021) - Akkerman, Hylke; Peeters, Bart; van Breemen, Albert; Shanmugam, Santhosh; Ugalde Lopez, Leslye; Tordera, Daniel; van de Ketterij, Richard; Delvitto, Ezequiel; Verbeek, Roy; Malinowski, Paweł; Ke, Tung‐Huei; De Roose, Florian; et al.
Abstract: In recent years there has been an increasing interest to integrate optical sensing in mobile displays, for instance, for biometric fingerprint scanning functionality. There are several routes to incorporate optical fingerprint functionality within the full display area, each with their own benefits and challenges. Here we investigate the different integration routes using large‐area, ultra‐thin imagers based on organic photodiodes. Abstract : There are several routes to incorporate optical fingerprint functionality within the full display area, each with their own benefits and challenges. Here we investigate the different integration routes using large‐area, ultra‐thin imagers based on organic photodiodes. The photograph shows a highly transparent imager for integration on top of low‐end displays.